Experimental Study on Fabrication and Comparison of Mechanical Properties of Plain Weave Copper Mesh Embedded Hybrid Composite with E-Glass Fiber Reinforced Epoxy GFRP Composite - Chopra, Ravindra; Kumar, Mukesh; Akhtar, Nahid (LPPM Universitas Andalas, 2021)
This paper presents the experimental study on on GFRP (Glass-Fiber Reinforced Plastic) composite which is fiberglass reinforced with epoxy matrix and find its mechanical properties that can be compared with other hybrid composite which include plain weave copper strips mesh in between the layers of fiberglass in GFRP composite. Both type of composites are made using hand layup technique i.e., placing of chopped fiberglass sheet and then epoxy resin layer by layer, after filling of epoxy and fiberglass at 20% fiber loading which is measured by digital scale, then a pressure is also applied on this sandwich. After 24 hours it is ready to be demolded and after 48 hrs. samples was cuts as per ASTM standards then testing was done on both GFRP and Hybrid composites to find their Mechanical & Physical Properties. Results shows improvement as we introduce plain weave copper strips mesh in between the GFRP laminate to make it hybrid.